Description of Hystripalpus chalkidicus new species from olive trees in Greece (Acari: Tenuipalpidae) - Hatzinikolis Ε.Ν. (ENTOMOLOGIA HELLENICA, 1985)
The female and deutonyph of Hystripalpus chalkidicus, new species, are described and illustrated. The species was found on an olive tree in Chalkidiki, Greece.